Moral Mathematics and Personal Identity: An Ethical Analysis of Minato's Actions Sealing Kyūbi in the Anime Naruto Shippūden - Achmad Rasyid Amirullah; Rofhani Rofhani (Vocational College of Diponegoro University, 2026)
In utilitarianism, actions are considered right to the extent that they maximize benefits for as many people as possible. However, every act of sacrifice raises a fundamental question: who benefits, and who suffers? The pursuit of collective good often overlooks the individuals who bear the burden of such decisions. Fiction often provides a space to reflect on these moral conflicts in concrete terms. A relevant example can be found in the Anime Naruto Shippuden, where Minato Namikaze seals the destructive Kyūbi into his newborn son, Naruto Uzumaki. This decision saves thousands of Konoha citizens but condemns Naruto to an isolated childhood, social rejection, and an unchosen identity. This article critically analyzes this dilemma through Derek Parfit's concepts of Moral Mathematics and personal identity. Using a qualitative approach and close reading as a thought experiment, this study analyzes episodes 168 and 246–249 of Naruto Shippuden to test moral rationality. The results of the analysis show that Minato's actions reflect the moral miscalculation criticized by Parfit, because individual suffering is reduced to an instrument for collective benefit. Minato's actions also violate the limits of moral autonomy that should be inherent in every individual. These findings show that works of fiction can serve as a reflective space for moral philosophy.